KNOWLEDGE, ATTITUDE, AND PERCEPTION OF NURSES AND PHYSICIANS REGARDING PHARMACEUTICAL-INITIATED CLINICAL RESEARCH IN UAE, QATAR, OMAN, BAHRAIN, AND JORDAN - SHEREEN HAMMAD (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the study was to understand the reasons for the limited number of pharmaceutical-initiated clinical studies in the Middle East region, by assessing the knowledge, attitudes, and perceptions related to pharmaceutical-initiated clinical trials among health-care professionals (HCPs) in UAE, Qatar, Oman, Bahrain, and Jordan. Methods: The study was conducted using an online questionnaire-based survey. The HCP respondents were from UAE, Qatar, Oman, Bahrain, and Jordan and had a good understanding of the English language. Descriptive statistical analysis was used to analyze the responses. Results: The HCPs were not inclined toward participation in clinical trials and research activities. The reasons for their limited participation included a lack of time, resources, and limited awareness about their legal protection associated with such studies, and the lack of necessary training and education related to clinical research. Conclusions: Although there is a willingness to participate in clinical trials conducted by pharmaceutical companies, HCPs face various ethical, administrative, and academic barriers. Addressing these issues would help increase the number of trials conducted in the Middle East region.